A unified access control mechanism - Abendroth, Joerg (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2005)
The widespread employment of the Internet facilitates collaboration and the use of distributed applications. Security concerns, such as controlled access to resources are preeminent. Often different applications employ different access control models, which are extended by each organisation or administration domain to enforce their own policies. Maintaining a coherent and non-complex access control policy becomes an increasingly difficult task.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin